Clinical-diagnostic criteria and peculiarities of treatment of urocystitis in cats - Shulzhenko, N. M.; ChernenkoО. М.; Holubyev, O. V.; BordunovaО. G.; Suslova, N. I. (Regulatory Mechanisms in Biosystems, 2019)
The results of a study of cats with signs of urocystitis are presented. The general principles of diagnostics based on clinical, laboratory and additional research methods are established. Clinically acute urocystitis was manifested by disorders of urination – pollakiuria, dysuria, stranguria. Some of the animals showed an increase in body temperature, pain in the bladder and tightness of the walls of the abdominal cavity. According to the results of urine study, it was observed that 43.7% of the cats with urocystitis showed an increase in relative density of the urine, a change in urine pH towards higher alkaline levels, urine residue – erythrocytes, leukocytes and microorganisms were indicated. Impurities of salt and sand were found in 58.4% of the cats. In 31.4% of the cats, urocystitis was a complication of urolithiasis. Early diagnosis, especially differential diagnosis of acute and chronic, secondary urocystitis presents difficulties. Therefore, in cases of suspected inflammatory diseases of the urinary tract, a complex examination using ultrasound of the kidneys, bladder, prostate gland (in males) and the uterus (in females) is recommended.With therapeutic purpose, sick cats (two groups of 8 animals/group) were administered: anti-microbial agent (5% solution of Enrofloxacin), spasmolytic medicinal agent – Riabal®. Animals of the second group were additionally administered the drug Cystocure (Candioli Farmaceutici). According to the instructions, the plant basis of the powder Cystocure is presented by extracts of cranberries and orange peels. These substances provide the main properties of the drug – help in resisting the bacterial colonization of the lower urinary tract and change in urine pH to the acid side. The applied therapy positively influenced the clinical condition of the cats. Their general health was improved, painful sensations during the act of urination disappeared, the quantity and frequency of diuresis normalized. On the seventh day of treatment, according to the results of the study, the urine became transparent, no microorganisms were detected. In cats of the second group, which additionally used the drug Cystocure, the amount of salts and sand decreased significantly, the pH of the urine did not exceed the recommended value of 6.4, in contrast to animals of the first group.